Kepemimpinan Kepala Sekolah SD Negeri 169 Pekanbaru - Nuramalina, Nuramalina; Ain, Siti Quratul; Adelia, Dela; Kusuma, Tiara; Shela, Yola Pramai (Indonesian Research Journal on Education, 2023)
Leadership is the most important part of running an organization. The organization in the form of an elementary school is led by a principal who is in charge of organizing, planning, and organizing hissubordinates to carry out their duties and achieve goals together. The quality of a school is closelyrelated to the principal. A good principal will certainly produce good school quality. On the contrary, a bad principal will certainly result in the quality of the school that has regressed or has not changed. The purpose of this study is to describe: (1) the Vision and Mission of Leadership in Schools, (2) the Leadership Style of the Principal, (3) The Principal's Leadership Approach, (4) The principal's skills, (5) The principal's leadership role, and (6) The principal's efforts in solving problems or conflicts in schools. The research method used is qualitative. The data collection techniques used in this study were interviewsand observations. The population or sample used in this study was the principal of SD Negeri 169Pekanbaru, named Mrs. Suryati, S. Pd., M. Si. Leadership Style affects the working qualities of each worker. For this reason, the selection of the right leadership style will affect a more positive and significant leadership process.